PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM PERUSAKAN LINGKUNGAN HIDUP - Gunawan, Lidya Pratiwi; Ratnawati Gultom, Elfrida (UNES Law Review, 2023)
The goal of this research is to investigate and determine the regulation of environmental offenses under Law 32 of 2009(known as environmental law) and how to be responsible for environmental crimes according to environmental law This research uses normative legal research methods using primary and secondary data, with descriptive analysis and deductive conclusions. Environmental crimes can be include within intentional or unintentional acts. Subjects of criminal law may be individuals, legal bodies, or non-legal entities. In this scenario, both legal entities and non-legal entities are companies. Responsibility in Article 88 means 'absolute accountability,' or the so-called "strict liability idea. Under the liability requirements of this article, the plaintiff is not necessary to prove the existence of an element of error as the basis for compensation. When the principle of strict liability is invoked, the legal subject is held accountable for pollution and environmental harm in the living environment in line with Article 88 of environmental legislation.